Coronariopatia assintomática em pacientes com cardiomiopatia chagásica em insuficiência cardíaca grave: prevalência e fatores de risco. - CARVALHO, Gustavo (2011)
Background: The concomitance of asymptomatic coronary heart disease in patients with Chagas cardiomyopathy with heart failure is not well known in medical literature, and both are very prevalent in some regions of Brazil. Objective: Determine the prevalence of coronary disease (lesion>50%) in a specific group of patients with Chagas cardiomyopathy and heart failure, in functional class III and IV, with no previous symptoms or diagnosis of coronaryopathy. Methods: Coronary angiography was performed in 61 consecutive patients with Chagas cardiomyopathy with heart failure, functional class III and IV, to exclude coronary heart disease. These patients were part of study protocol of cell therapy in heart disease, which required the implementation of coronary angiography before injecting stem cells. Risk factors for atherosclerosis also analyzed in this population were: age, hypertension, diabetes, dyslipidemia, smoking and overweight. Results: ages 51.6 + 9.6 years 65.5%(n = 40) men. The prevalence of coronary disease found in this population was 1.6%(1). The prevalence of risk factors were: hypertension 18%(11), smoking 59%(36), diabetes 1.6%(1) and dyslipidemia 6.5%(4). Conclusion: The prevalence of asymptomatic coronary disease in patients with chagasic etiology severe heart failure is low and among the risk factors for coronary heart disease, smoking was the most prevalent.